2001
DOI: 10.1073/pnas.041327398
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal regulation of Na+-Ca2+ exchanger by beta -adrenergic signaling pathway in shark ventricular myocytes

Abstract: In shark heart, the Na ؉ -Ca 2؉ exchanger serves as a major pathway for both Ca 2؉ influx and efflux, as there is only rudimentary sarcoplasmic reticulum in these hearts. The modulation of the exchanger by a ␤-adrenergic agonist in whole-cell clamped ventricular myocytes was compared with that of the Na ؉ -Ca 2؉ exchanger blocker KB-R7943. Application of 5 M isoproterenol and 10 M KB-R7943 suppressed both the inward and the outward Na ؉ -Ca 2؉ exchanger current (I Na؊Ca ). The isoproterenol effect was mimicked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It would also be in agreement with the absence, in both the trout and mammalian NCX protein (Nicoll et al, 1990;Xue et al, 1999), of the putative PKA-dependent phosporylation site described in frog (Fan et al, 1996). It is, however, contrary to results from the frog heart, where a putative PKA-dependent phosporylation site on the NCX has been described (Fan et al, 1996) and a PKA-dependent inhibition of NCX activity has been reported in both frog and shark cardiac myocytes (Fan et al, 1996;Woo and Morad, 2001). The present results also show that the importance of SR Ca 2+ uptake relative to sarcolemmal Ca 2+ extrusion by the NCX is unchanged with β-adrenergic stimulation in trout atrial myocytes.…”
Section: Indirect Effects Of β-Adrenergic Stimulation On Sr Casupporting
confidence: 84%
“…It would also be in agreement with the absence, in both the trout and mammalian NCX protein (Nicoll et al, 1990;Xue et al, 1999), of the putative PKA-dependent phosporylation site described in frog (Fan et al, 1996). It is, however, contrary to results from the frog heart, where a putative PKA-dependent phosporylation site on the NCX has been described (Fan et al, 1996) and a PKA-dependent inhibition of NCX activity has been reported in both frog and shark cardiac myocytes (Fan et al, 1996;Woo and Morad, 2001). The present results also show that the importance of SR Ca 2+ uptake relative to sarcolemmal Ca 2+ extrusion by the NCX is unchanged with β-adrenergic stimulation in trout atrial myocytes.…”
Section: Indirect Effects Of β-Adrenergic Stimulation On Sr Casupporting
confidence: 84%
“…Therefore, the suppression of inward I Na–Ca by 8‐Br‐cAMP, and the resulting shift of the reversal potential, in part reflects a decrease in the amount of Ca 2+ brought into the cell during the conditioning pulse (cf. Woo & Morad, 2001). The results in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, CA modify the vasoactivity of the coronary system [welldeveloped in elasmobranchs ], thus adjusting coronary performance to myocardium requirements (Axelsson, 1995). An electrophysiological study in sharks (Woo and Morad, 2001) (Woo and Morad, 2001).…”
Section: Adrenergic Neuroendocrine Patternsmentioning
confidence: 99%